Tradisi Bona Taon Suku Batak Toba Di Perkotaan: Antara Kekerabatan Dan Citra - Mangihut Siregar (Universitas Andalas, 2022)
Kinship is essential for the Toba Batak tribe. To maintain kinship, good relations between those who live in the area of origin and those who live in the overseas (urban) areas are always maintained. This sound kinship brings traditions from the area of origin to the overseas area. One of the exciting traditions to study is the Bona Taon. This tradition has long been lost in the area of origin but is increasingly existent in urban areas. The Bona Taon tradition was lost because of the prohibition by the Dutch colonialists. This study examines the Bona Taon tradition of urban-plan models using globalization theory and hypersemiotic theory. The results show that the Bona Taon tradition carried out by the Batak tribe in urban areas aims to strengthen kinship relationships that are full of images. In practice, this tradition has changed from what was originally sacred to only entertainment.